Analisis Kebutuhan Pengembangan Laboratorium PGMI dalam Perkuliahan IPA - Suyatman Suyatman (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2016)
Based on documentation of pgmi mentioned that college students are derived from background science class is 36,98 % , less than 50 % of the student PGMI .This has led consequence that lecture believe in science ranging from the base and supported by the laboratory adequate .The laboratory adequate will build real kosep students in understand science.Steps analysis needs research laboratory PGMI in lecture ipa is as follows: 1) analysis of need assessment, 2) the literature study, 3) study komparasi , 4) expert judgment, 5) improvement. Based on analysis of the data can pull conclusions as follows:  1) The lab PGMI FITK IAIN Surakarta especially for science laboratory having 85 set equipment consisting of 737 the tools and can be used to 121 title science experiments. 2) Additional needs necessary the 25 set equipment science experiments, with details as follows: kit science less 24 set, consisting of the balance KIT  4 sets, mineral KIT  5 sets, Sound KIT  4 sets, coal KIT  6 sets, and  heat engine  KIT 5 sets, and science integrated KIT less 1 set, and 5 the microscopes.Keywords: analysis needs , the development of a laboratory, IPA  lecture